Corporate ethics for turbulent markets : the market context of executive decisions - Mascarenhas, Oswald A. J. (Emerald Publishing Limited, 2018)
The tapestry of human behaviour in the marketplace today is turbulent, unpredictable, and chaotic. Yet it is also so diverse, rich and global that it presents a rare ethical and moral opportunity, and challenge, to out-behave competition and create enduring value. This is corporate ethics for corporate advantage. Corporate Ethics for Turbulent Markets: The Market Context of Executive Decisions focuses on the HOW of doing business the economic, social, ethical, moral and spiritual values we bring to our business ventures - and how thereby we impact the world. The book focuses on the LEMS (legality, ethicality, morality, and spirituality) technique that we submit as a prescriptive benchmarking tool for all corporate thinking, deliberation, explanation, evaluation, choices, strategic implementation, accountability and moral responsibility. It demonstrates that by going beyond the legal obligation (legality) to do the "right thing" (ethicality), to do the "right thing rightly" (morality), and doing the "right thing rightly and for the right intentions" (spirituality), we can create a sure strategy for good decision making and implementation that can heal the world from its current addictions to corporate fraud in all its evil forms. Envisioning a moral reawakening, this book will challenge business students and executives alike to re-evaluate the moral justification of business choices, decisions, actions and their consequences. LEMS as a four-dimensional cross-checking skill for all that we think, do, become and be takes time and patience but it can surely heal an otherwise divided and broken world.
Includes bibliographical references and indexes.
Print version record
Keywords: Business ethics; Business & Economics -- Organizational Behavior; Organizational theory & behaviour